Selective Attention and Inhibitory Control of Attention Are Correlated With Music Audiation - Grinspun, Noemí; Nijs, Luc; Kausel, Leonie; Onderdijk, Kelsey; Sepúlveda, Nicolás; Rivera-Hutinel, Antonio (Frontiers in Psychology, 2020)
Executive functions (EFs) are cognitive functions needed for adaptive and targeted behavior. Music aptitude is the potential or capacity for musical achievement. A key element of music aptitude is audiation, defined as the process through which sound becomes music and meaning is attributed to that music. In this paper, we report on the association between audiation skills and executive skills. Not only is this important to consider the validity of the audiation tests, but also to better understand the concept of audiation and its link to cognitive skills. We conducted an empirical study, in which a sample of second grade school students from two elementary schools, one from Ghent, Belgium (N = 36) and the other from Santiago, Chile (N = 25), were administered both a musical aptitude and an attention and inhibitory control test. We hypothesized that a positive correlation exists between sustained attention, inhibitory control and music aptitude.